2014
DOI: 10.1167/iovs.14-15709
|View full text |Cite
|
Sign up to set email alerts
|

Preparative and Biosynthetic Insights Into pdA2E and isopdA2E, Retinal-Derived Fluorophores of Retinal Pigment Epithelial Lipofuscin

Abstract: Our results facilitate the understanding of compositions and biosynthetic pathways of adverse RPE lipofuscin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…and its isomers, all-trans-retinal dimer, A2-DHP-PE, A2-GPE, and pdA2E and its isomer, have been isolated and identified structurally. 32,46,[51][52][53][54][55][56][57][58] Because of their relatively high physiological significance, the in vitro cytotoxicity and phototoxicity of A2E have been extensively investigated. [59][60][61][62][63][64] It is of note that retinal-derived lipofuscin fluorophores accumulate to a less extent in eyes of wild-type mice than Abca4 gene knockout mice.…”
Section: The Metabolism Of Retinoids In the Retinamentioning
confidence: 99%
“…and its isomers, all-trans-retinal dimer, A2-DHP-PE, A2-GPE, and pdA2E and its isomer, have been isolated and identified structurally. 32,46,[51][52][53][54][55][56][57][58] Because of their relatively high physiological significance, the in vitro cytotoxicity and phototoxicity of A2E have been extensively investigated. [59][60][61][62][63][64] It is of note that retinal-derived lipofuscin fluorophores accumulate to a less extent in eyes of wild-type mice than Abca4 gene knockout mice.…”
Section: The Metabolism Of Retinoids In the Retinamentioning
confidence: 99%
“…1B), 14 A2-DHP-PE, 15 pdA2E, 16 and isopdA2E. 17 In all of these pigments, the most intense and extensive studies are directed to A2E due to its abundance and typical age-dependent accumulation in humans, 18 and C57BL/ 6J and BALB/cByJ wild-type (WT) mice. 15 Previous studies have indicated that Abca4 À/À Rdh8 À/À double-knockout (DKO) mice reproduce the main features of human AMD in a rodent model.…”
mentioning
confidence: 99%